Child Custody Due to Divorce in Indonesia Post the Constitutional Court Decision Number 140/PUU-XXI/2023 from a Human Rights Perspective - Miqat, Nurul; Susilawati, Susi; Nokoe, Nurhayati Sutan; Fadjar, Adfiyanti; Datupalinge, Suarlan; Patila, Manga (International Journal of Science and Society, 2025)
Article 1 of Marriage Law Number 16 of 2019 amending the Marriage Law 1 of 1974, states that marriage is a marriage is a physical and mental bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on God Almighty, a marriage that is built based on physical and mental bonds, with the aim of being eternal, and getting offspring that can continue generations. However, not all existing marriages run smoothly as expected, the many obstacles and trials in every household sometimes trigger a divorce, which consequently has an impact on one of the children born. As a result, many divorced couples feel entitled to child custody. This paper takes the formulation of the problem of how child custody due to divorce, after the decision of the Constitutional Court Number 140/PUU-XXI/2023 from the perspective of Human Rights. This paper uses a normative juridical writing method with a statutory approach.